PBAT and black talcum powder composite material and preparation method thereof
Through the melt mixing of modified black talc powder and PBAT resin and the modification of nano zinc oxide, the aging problem of PBAT/black talc powder composite in complex environments is solved, high mechanical and aging resistance is achieved, and thermal insulation is improved Effect, suitable for the application of agricultural land film.
Patent Information
- Application Number
- CN202411411779.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2024-12-20
AI Technical Summary
The existing PBAT/black talc composite agricultural land film is prone to holes and cracks under complex environmental conditions, and the tensile strength decreases, making it difficult to meet the application requirements in the agricultural field.
Modified black talc powder and PBAT resin were melt-mixed with dopamine hydrochloride solution and KMnO4 solution, combined with modified nano zinc oxide and antioxidant, and modified black talc powder masterbatch and nano zinc oxide were prepared by intricate extrusion. Form a reactive composite material to enhance mechanical and aging resistance.
The good mechanical properties, excellent aging resistance and good thermal insulation properties of PBAT/black talc composites were achieved, and the fracture strength was maintained between 6.77 and 7.03N, and the fracture strength was not less than 4.74N after 5D UV accelerated aging. The film was tested in 60D field. There are no holes or cracks behind, and the insulation effect is improved.
Smart Images

Figure BDA0005078207730000081 
Figure BDA0005078207730000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of film-making materials, and in particular to a PBAT and black talcum powder composite material and a preparation method thereof. Background Art
[0002] Polybutylene adipate / terephthalate (PBAT) resin is synthesized from raw materials such as 1,4-butanediol, terephthalic acid and p-hydroxybutyric acid. It is a biodegradable polyester resin that can be decomposed into water, carbon dioxide and biomass under appropriate conditions. In the context of global carbon neutrality, PBAT resin has been widely used, including disposable food packaging, agricultural films, shopping bags and other degradable plastic products.
[0003] Black talcum powder is a dark gray or black mineral powder, the main component of which is magnesium silicate. This material is widely available, inexpensive and environmentally friendly. At the same time, due to its unique dark gray or black luster, it has a warming and heat preservation effect. It has been tried to be used in degradable agricultural films, such as PBAT / black talcum powder composite agricultural films. However, there are some problems in the application process. Since black talcum powder contains components such as variable metals and organic matter, it will accelerate the degradation and aging of the composite film under complex environmental conditions (ultraviolet rays, microorganisms, etc.), resulting in holes and cracks in the life cycle of the agricultural film (≥60 days) or the tensile strength retention rate of the composite film after aging is less than 50%, which does not meet the actual application requirements and is not conducive to the promotion and application of composite agricultural films in the agricultural field. Summary of the invention
[0004] Therefore, in order to solve the above problems, the present invention provides a PBAT and black talcum powder composite material and a preparation method thereof. The PBAT and black talcum powder composite material prepared by the method of the present invention has good mechanical strength, excellent aging resistance and thermal insulation performance, and can be used in the production of agricultural land film.
[0005] To solve this technical problem, the present invention adopts the following scheme: a PBAT and black talc composite material, comprising the following raw material components in weight percentage: 60wt%-75wt% PBAT resin, 20wt%-35wt% modified black talc masterbatch, 1wt%-5wt% modified nano zinc oxide, 0.5wt%-2wt% antioxidant, 0.5wt%-2wt% liquid paraffin;
[0006] The modified black talc masterbatch is prepared by melting and mixing the modified black talc with PBAT resin after the modified black talc is modified by dopamine hydrochloride solution and KMnO4 solution through a mixing and extrusion integrated machine.
[0007] The modified nano zinc oxide is prepared by modifying nano zinc oxide through dopamine hydrochloride solution and ethylene glycol diglycidyl ether.
[0008] Furthermore, the pH of the dopamine hydrochloride solution in the modified black talc masterbatch is 8-9, the mass ratio of black talc to dopamine hydrochloride solution is 0.2-0.4:1, the mass ratio of KMnO4 to dopamine is 0.2-0.4:1, and the mass ratio of modified black talc to PBAT resin is 3-4:1.
[0009] Furthermore, the average particle size of the modified black talcum powder is 3000-6000 mesh.
[0010] Furthermore, the pH of the dopamine hydrochloride solution in the modified nano zinc oxide is 8-9, the mass ratio of ethylene glycol diglycidyl ether to dopamine hydrochloride solution is 0.03-0.05:1, and the mass ratio of nano zinc oxide to dopamine hydrochloride solution is 0.1-0.2:1.
[0011] Furthermore, in step 3, the average particle size of the modified nano zinc oxide is 100-300 nm.
[0012] Furthermore, the antioxidant is at least one of antioxidant 1010 , antioxidant 4426 and antioxidant 1330 .
[0013] The above-mentioned PBAT and black talcum powder composite material is used in the production of agricultural land film.
[0014] The preparation method of the above-mentioned PBAT and black talcum powder composite material comprises the following steps:
[0015] Step 1, preparation of modified black talcum powder masterbatch: add black talcum powder to 2g / L dopamine hydrochloride solution, then add KMnO4 solution, stir at room temperature for 2-4h, filter and wash with deionized water and dry, and crush with a pulverizer to obtain modified black talcum powder; melt-mix the modified black talcum powder and PBAT resin through a banburying extruder, and the extrusion temperature is 100-150°C to obtain a modified black talcum powder masterbatch;
[0016] Preparation of modified nano zinc oxide: Add nano zinc oxide to 2g / L dopamine hydrochloride solution, stir at room temperature for 2-4h, then add ethylene glycol diglycidyl ether and stir at 50-70°C for 2-6h, then filter and wash with deionized water, dry, and crush with a grinder to obtain modified nano zinc oxide;
[0017] Step 2: melt-mix and granulate 60wt%-75wt% PBAT resin, 20wt%-35wt% modified black talc masterbatch, 1wt%-5wt% modified nano zinc oxide, 0.5wt%-2wt% antioxidant, and 0.5wt%-2wt% liquid paraffin at a processing temperature of 105-165° C. to obtain a finished PBAT and black talc composite material.
[0018] Furthermore, when the modified black talcum powder masterbatch is prepared in step 1, the pH of the dopamine hydrochloride solution is 8-9, the mass ratio of black talcum powder to dopamine hydrochloride solution is 0.2-0.4:1, the mass ratio of KMn04 to dopamine is 0.2-0.4:1, and the mass ratio of modified black talcum powder to PBAT resin is 3-4:1.
[0019] Furthermore, when preparing the modified nano zinc oxide in step 1, the pH of the dopamine hydrochloride solution is 8-9, the mass ratio of ethylene glycol diglycidyl ether to dopamine hydrochloride solution is 0.03-0.05:1, and the mass ratio of nano zinc oxide to dopamine hydrochloride solution is 0.1-0.2:1.
[0020] By adopting the above technical solution, the beneficial effects of the present invention are:
[0021] 1. Good mechanical properties. The surface of black talc powder is modified by dopamine hydrochloride and combined with PBAT resin by mixing and extrusion to prepare modified black talc powder masterbatch, which can not only enhance the interface between black talc powder and PBAT matrix resin, but also improve the uniform dispersion of powder in PBAT resin; at the same time, by modifying nano zinc oxide and introducing reactive functional groups, PBAT resin can form micro cross-links, and the good mechanical properties of PBAT and black talc powder composite materials are achieved under the comprehensive effect, so that the fracture strength of PBAT and black talc powder composite materials is 6.77~7.03N.
[0022] 2. Excellent aging resistance. In the KMnO4 solution environment, dopamine hydrochloride is rapidly oxidized and cross-linked and coated on the surface of black talcum powder to form a polydopamine coating, which effectively inhibits the accelerated catalytic degradation of PBAT molecular chains by black talcum powder under the action of ultraviolet rays and improves its anti-ultraviolet level; at the same time, by adding nano zinc oxide with the ability to absorb ultraviolet rays, the degradation effect of external ultraviolet rays on PBAT molecular chains is reduced, and the composite material is given antibacterial properties to reduce the negative impact of external microorganisms on the composite material. In addition, the introduction of reactive functional groups on the surface of nano zinc oxide can realize the formation of micro-crosslinks of PBAT molecular chains. Under the combined effect, the PBAT and black talcum powder composite material has excellent aging resistance. The breaking strength of the PBAT and black talcum powder composite material is maintained at 4.74~5.06N after 5d of ultraviolet accelerated aging, and no holes or cracks were found in the film after 60d of field tests.
[0023] 3. Good thermal insulation performance. On the one hand, since black talcum powder inherently exhibits a good black luster, it can increase the grayscale of the PBAT and black talcum powder composite material, prompting the composite material to absorb light energy and convert it into geothermal energy, releasing heat to the soil, thereby increasing the surface soil temperature; on the other hand, the surface-modified black talcum powder, nano zinc oxide and PBAT matrix resin have good compatibility, which can inhibit the micropore phenomenon caused by casting or blow molding, reduce heat exchange channels, and reduce the heat dissipation of the surface soil to the outside, thereby achieving good thermal insulation performance of the PBAT and black talcum powder composite material. The PBAT and black talcum powder composite material can maintain the soil heat capacity at 0.61-0.65 cal·cm -3 ℃ -1 Status above. DETAILED DESCRIPTION
[0024] In order to further illustrate the present invention, the present invention is further described in conjunction with specific implementation modes.
[0025] Example 1
[0026] The PBAT / black talcum powder composite material includes the following raw material components in weight percentage: 70wt% PBAT resin, 24wt% modified black talcum powder masterbatch, 3wt% modified nano zinc oxide, 1wt% antioxidant 4426, and 2wt% liquid paraffin.
[0027] A method for preparing a PBAT / black talcum powder composite material comprises the following steps:
[0028] Step 1, prepare a modified black talcum powder masterbatch: add black talcum powder to 2g / L dopamine hydrochloride solution (pH=8.5) at a mass ratio of 0.3:1, then add 0.4g / L KMnO4 solution, stir at room temperature for 4h, filter and wash with deionized water and dry, and grind with a grinder to obtain modified black talcum powder (6000 mesh), and melt-mix the modified black talcum powder and PBAT resin through a banburying extruder at a mass ratio of 4:1, and the extrusion temperatures are 100°C, 120°C, 135°C, 145°C, 145°C, and 150°C to obtain a modified black talcum powder masterbatch;
[0029] Preparation of modified nano zinc oxide: zinc oxide was added to 2 g / L dopamine hydrochloride solution (pH=8.5) at a mass ratio of 0.1:1, stirred at room temperature for 3 h, then ethylene glycol diglycidyl ether (4 wt% of dopamine hydrochloride solution) was added and stirred at 65°C for 6 h, filtered, washed with deionized water, dried, and crushed with a pulverizer to obtain modified nano zinc oxide (300 nm);
[0030] Step 2: 70wt% PBAT, 24wt% modified black talc masterbatch, 3wt% modified nano zinc oxide, 1wt% antioxidant 4426, and 2wt% liquid paraffin are melt-mixed and granulated at processing temperatures of 105°C, 120°C, 140°C, 155°C, 165°C, and 160°C to obtain a PBAT / black talc composite material.
[0031] Example 2
[0032] The PBAT / black talcum powder composite material includes the following raw material components in weight percentage: 75wt% PBAT resin, 20wt% modified black talcum powder masterbatch, 2wt% modified nano zinc oxide, 1.5wt% antioxidant 1330, and 1.5wt% liquid paraffin.
[0033] The preparation method of the PBAT / black talcum powder composite material comprises the following steps:
[0034] Step 1, prepare a modified black talcum powder masterbatch: add black talcum powder to 2g / L dopamine hydrochloride solution (pH=8.5) at a mass ratio of 0.2:1, then add 0.8g / L KMnO4 solution, stir at room temperature for 3.5h, filter and wash with deionized water and dry, and grind with a pulverizer to obtain modified black talcum powder (3000 mesh), and melt-mix the modified black talcum powder and PBAT resin through a banburying extruder at a mass ratio of 3:1, and the extrusion temperatures are 100°C, 118°C, 136°C, 145°C, 148°C, and 150°C to obtain a modified black talcum powder masterbatch;
[0035] Preparation of modified nano zinc oxide: zinc oxide was added to 2 g / L dopamine hydrochloride solution (pH=8.5) at a mass ratio of 0.2:1, stirred at room temperature for 2 h, then ethylene glycol diglycidyl ether (5 wt% of dopamine hydrochloride solution) was added and stirred at 70°C for 2 h, filtered, washed with deionized water, dried, and crushed with a pulverizer to obtain modified nano zinc oxide (100 nm);
[0036] Step 2: 75wt% PBAT, 20wt% modified black talc masterbatch, 2wt% modified nano zinc oxide, 1.5wt% antioxidant 1330, and 1.5wt% liquid paraffin are melt-mixed and granulated at processing temperatures of 105°C, 123°C, 142°C, 156°C, 165°C, and 162°C to obtain a PBAT / black talc composite material.
[0037] Example 3
[0038] The PBAT / black talc composite material comprises the following raw material components in weight percentage: 60wt% PBAT resin, 33wt% modified black talc masterbatch, 5wt% modified nano zinc oxide, 1wt% antioxidant 1010, and 1wt% liquid paraffin.
[0039] The preparation method of the PBAT / black talcum powder composite material comprises the following steps:
[0040] Step 1, preparing a modified black talcum powder masterbatch: adding black talcum powder to 2 g / L dopamine hydrochloride solution (pH=8.5) at a mass ratio of 0.4:1, then adding 0.5 g / L KMnO4 solution, stirring at room temperature for 2 hours, filtering and washing with deionized water and drying, and crushing with a pulverizer to obtain modified black talcum powder (5000 mesh), and melt-mixing the modified black talcum powder and PBAT resin through a banburying extruder at a mass ratio of 3.6:1, and the extrusion temperatures are 100°C, 124°C, 138°C, 146°C, 150°C, and 147°C to obtain a modified black talcum powder masterbatch;
[0041] Preparation of modified nano zinc oxide: zinc oxide was added to 2 g / L dopamine hydrochloride solution (pH=8.5) at a mass ratio of 0.12:1, stirred at room temperature for 3.5 h, then ethylene glycol diglycidyl ether (3 wt% of dopamine hydrochloride solution) was added and stirred at 50°C for 4 h, filtered, washed with deionized water, dried, and crushed with a pulverizer to obtain modified nano zinc oxide (200 nm);
[0042] Step 2: 60wt% PBAT, 33wt% modified black talc masterbatch, 5wt% modified nano zinc oxide, 1wt% antioxidant 1010, and 1wt% liquid paraffin are melt-mixed and granulated at processing temperatures of 105°C, 125°C, 146°C, 153°C, 165°C, and 163°C to obtain a PBAT / black talc composite material.
[0043] Comparative Example 1
[0044] In this comparative example, the PBAT resin is directly extruded and granulated through a twin-screw extruder at processing temperatures of 105° C., 120° C., 140° C., 155° C., 165° C., and 160° C. to prepare the PBAT material.
[0045] Comparative Example 2
[0046] The difference from Example 1 is that the raw black talc powder of Comparative Example 2 is not surface modified, other operations and proportions remain unchanged, and the processing temperatures are 105°C, 120°C, 140°C, 155°C, 165°C, and 160°C to prepare PBAT / black talc powder composite materials.
[0047] Comparative Example 3
[0048] The difference from Example 1 is that the raw material black talc powder of Comparative Example 3 is not added with KMnO4 solution during surface modification, other operations and proportions remain unchanged, and the processing temperatures are 105°C, 120°C, 140°C, 155°C, 165°C, and 160°C to prepare PBAT / black talc powder composite materials.
[0049] Comparative Example 4
[0050] The difference from Example 1 is that the modified black talc powder of Comparative Example 4 is not extruded into a masterbatch through internal mixing, and the modified black talc powder is directly used to replace the modified black talc powder masterbatch, and the other operations and proportions remain unchanged. The processing temperatures are 105°C, 120°C, 140°C, 155°C, 165°C, and 160°C to prepare PBAT / black talc composite materials.
[0051] Comparative Example 5
[0052] The difference from Example 1 is that in Comparative Example 5, modified nano zinc oxide is not added, other operations and proportions remain unchanged, and the processing temperatures are 105°C, 120°C, 140°C, 155°C, 165°C, and 160°C to prepare PBAT / black talc composite materials.
[0053] Comparative Example 6
[0054] The difference from Example 1 is that the nano zinc oxide in Comparative Example 6 is not modified by dopamine and ethylene glycol diglycidyl ether, the other operations and proportions remain unchanged, and the processing temperatures are 105°C, 120°C, 140°C, 155°C, 165°C, and 160°C to prepare PBAT / black talc composite materials.
[0055] 2. Performance Test
[0056] The PBAT / black talc composite materials prepared in each embodiment and comparative example were cast or blown into a film of about 0.008 mm, and cut into standard specimens to measure the breaking strength (GB / T 1040.3-2006) and antibacterial effect (GB / T 31402-2015) of the film. At the same time, the surface damage of the film was observed after 60 days of field test. In addition, the heat capacity of the soil after the film was covered was measured by a temperature detector. The results are shown in Table 1.
[0057] Table 1 List of test results of each sample
[0058]
[0059]
[0060] It can be seen from the data in Table 1 that the PBAT / black talcum powder composite materials prepared in Examples 1 to 3 have good mechanical properties, excellent aging resistance and good thermal insulation properties, and meet the application requirements of agricultural films. Among them, the breaking strength of the modified film is not less than 6.77N, basically maintained at 6.77~7.03N, the breaking strength after 5d UV accelerated aging is not less than 4.74N, basically maintained at 4.74~5.06N, the antibacterial effect is not less than 95.7%, basically maintained at 95.7~98.5%, and the thermal insulation effect is not less than 0.61cal·cm-3·℃-1, basically maintained at 0.61~0.65cal·cm-3·℃-1. In addition, no holes or cracks were found in the film after 60d field test.
[0061] From Comparative Example 1, it can be found that the original breaking strength of pure PBAT material is low, the strength decreases rapidly after UV aging, there is no antibacterial effect, there are holes or cracks in the 60d field test, and the thermal insulation effect is poor, which makes it difficult to achieve agricultural mulch film application. By modifying PBAT, the above shortcomings are effectively overcome, as shown in Examples 1 to 3 in Table 1. Compared with Example 1, in Comparative Example 2, under the condition that the black talcum powder is not modified, the breaking strength of the film after UV accelerated aging decreases rapidly, and there are holes or cracks in the 60d field test and the thermal insulation effect is reduced; in Comparative Example 3, under the condition that KMnO4 solution is not added, the breaking strength of the film after UV accelerated aging decreases rapidly, and there are partial cracks in the 60d field test and the thermal insulation effect is reduced; in Comparative Example 4, under the condition that the modified black talcum powder is not extruded into a masterbatch without mixing, all aspects of the film performance are reduced; in Comparative Example 5, under the condition that nano zinc oxide is not added, the film has no antibacterial effect, and there are holes or cracks in the 60d field test; in Comparative Example 6, under the condition that nano zinc oxide is not modified by dopamine and ethylene glycol diglycidyl ether, the breaking strength of the film after UV accelerated aging decreases rapidly, there are partial cracks in the 60d field test and the thermal insulation effect is reduced.
[0062] The PBAT / black talc composite material of the present invention is composed of the following raw material components in weight percentage: 60wt%-75wt% PBAT resin, 20wt%-35wt% modified black talc masterbatch, 1wt%-5wt% modified nano zinc oxide, 0.5wt%-2wt% antioxidant, and 0.5wt%-2wt% liquid paraffin;
[0063] The pH of dopamine hydrochloride solution in the modified black talcum powder masterbatch is preferably 8-9, the mass ratio of black talcum powder to dopamine hydrochloride solution is preferably 0.2-0.4:1, the mass ratio of KMn04 to dopamine is preferably 0.2-0.4:1, the mass ratio of modified black talcum powder to PBAT resin is preferably 3-4:1, the average particle size of modified black talcum powder is preferably 3000-6000 mesh, and the modified nano zinc oxide is preferably 0. The pH of dopamine hydrochloride solution is preferably 8-9, the mass ratio of ethylene glycol diglycidyl ether to dopamine hydrochloride solution is preferably 0.03-0.05:1, the mass ratio of nano zinc oxide to dopamine hydrochloride solution is preferably 0.1-0.2:1, the average particle size of modified nano zinc oxide is preferably 100-300nm, and the antioxidant can be at least one of antioxidant 1010, antioxidant 4426 and antioxidant 1330.
[0064] Although the present invention has been specifically shown and described in conjunction with the preferred embodiments, it should be understood by those skilled in the art that various changes may be made to the present invention in form and details without departing from the spirit and scope of the present invention as defined by the appended claims, all of which are within the scope of protection of the present invention.
Claims
1. A composite material of PBAT and black talcum powder, characterized in that: The invention comprises the following raw material components in weight percentage: 60 wt%-75 wt% PBAT resin, 20 wt%-35 wt% modified black talc masterbatch, 1 wt%-5 wt% modified nano zinc oxide, 0.5 wt%-2 wt% antioxidant, and 0.5 wt%-2 wt% liquid paraffin; The modified black talc masterbatch is prepared by melting and mixing the modified black talc with PBAT resin after the modified black talc is modified by dopamine hydrochloride solution and KMnO4 solution through a mixer and extruder. The modified nano zinc oxide is prepared by modifying nano zinc oxide through dopamine hydrochloride solution and ethylene glycol diglycidyl ether.
2. The PBAT and black talc composite material according to claim 1, characterized in that: The pH of the dopamine hydrochloride solution in the modified black talc masterbatch is 8-9, the mass ratio of black talc to dopamine hydrochloride solution is 0.2-0.4:1, the mass ratio of KMnO4 to dopamine is 0.2-0.4:1, and the mass ratio of modified black talc to PBAT resin is 3-4:
1.
3. The PBAT and black talc composite material according to claim 2, characterized in that: The average particle size of the modified black talcum powder is 3000-6000 meshes.
4. The PBAT and black talc composite material according to claim 1, characterized in that: The pH value of the dopamine hydrochloride solution in the modified nano zinc oxide is 8-9, the mass ratio of ethylene glycol diglycidyl ether to the dopamine hydrochloride solution is 0.03-0.05:1, and the mass ratio of the nano zinc oxide to the dopamine hydrochloride solution is 0.1-0.2:
1.
5. The PBAT and black talc composite material according to claim 4, characterized in that: In step 3, the average particle size of the modified nano zinc oxide is 100-300 nm.
6. The PBAT and black talc composite material according to claim 1, characterized in that: The antioxidant is at least one of antioxidant 1010 , antioxidant 4426 and antioxidant 1330 .
7. The PBAT and black talc composite material according to any one of claims 1 to 6 is used in the production of agricultural land film.
8. A method for preparing the composite material of PBAT and black talc according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1, preparation of modified black talcum powder masterbatch: adding black talcum powder to 2g / L dopamine hydrochloride solution, then adding KMnO4 solution, stirring at room temperature for 2-4h, filtering and washing with deionized water and drying, and crushing with a pulverizer to obtain modified black talcum powder; melt-mixing the modified black talcum powder and PBAT resin through a banburying extruder at an extrusion temperature of 100-150°C to obtain a modified black talcum powder masterbatch; Preparation of modified nano zinc oxide: Add nano zinc oxide to 2g / L dopamine hydrochloride solution, stir at room temperature for 2-4h, then add ethylene glycol diglycidyl ether and stir at 50-70°C for 2-6h, then filter and wash with deionized water, dry, and crush with a grinder to obtain modified nano zinc oxide; Step 2: 60 wt%-75 wt% PBAT resin, 20 wt%-35 wt% modified black talcum powder masterbatch, 1 wt%-5 wt% modified nano zinc oxide, 0.5 wt%-2 wt% antioxidant, and 0.5 wt%-2 wt% liquid paraffin are melt-mixed and granulated at a processing temperature of 105-165° C. to obtain a finished PBAT and black talcum powder composite material.
9. The method for preparing the composite material of PBAT and black talc according to claim 8, characterized in that: When preparing the modified black talc masterbatch in step 1, the pH of the dopamine hydrochloride solution is 8-9, the mass ratio of black talc to dopamine hydrochloride solution is 0.2-0.4:1, the mass ratio of KMnO4 to dopamine is 0.2-0.4:1, and the mass ratio of modified black talc to PBAT resin is 3-4:
1.
10. The PBAT and black talc composite material according to claim 8, characterized in that: When preparing the modified nano zinc oxide in step 1, the pH of the dopamine hydrochloride solution is 8-9, the mass ratio of ethylene glycol diglycidyl ether to dopamine hydrochloride solution is 0.03-0.05:1, and the mass ratio of nano zinc oxide to dopamine hydrochloride solution is 0.1-0.2:1.
